Praktik Sosial Sahabat Kapas dalam Pendampingan Anak-Anak dalam Kondisi Khusus dan Rentan di Surakarta - Nurul Istiqomah; Bagus Haryono; Argyo Demartoto (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
Vulnerable Children and Children with Special Condition (Anak-Anak dalam Kondisi Khusus dan Rentan or AKKR) are children who must receive assistance and motivation to achieve their rights. In practice in real life, they are temporarily forced to be in correctional institutions/detention centers/Institute for Special Development Children (LPKA) as a result of violating the law. It should not make them shunned, but instead, they must be assisted. Vulnerable Children and Children with Special Condition need enforcement of the fulfillment of their rights. The existence of Sahabat Kapas as a nonprofit non-governmental organization (NGO) located in Karanganyar, Central Java, Indonesia, provides concerns and solicitudes for Vulnerable Children and Children with Special Condition. This research aims to analyze and describe the forms of social practice based on habitus in Sahabat Kapas organization. This research used a qualitative research method with Bourdieu’s genetic structuralism approach. Informants were determined using purposive sampling techniques. Data collection was performed using participant observation techniques in the field, in-depth interviews, and documentation studies. Data were analyzed in three stages, including data reduction, data presentation, and ended with concluding. Data were verified by source triangulation. The results showed that Sahabat Kapas became an alternative to assist Vulnerable Children and Children with Special Condition conducted in correctional institutions/detention centers/Institute for Special Development Children (LPKA). The social practices conducted by Sahabat Kapas in assisting Vulnerable Children and Children with Special Condition are following the capital they have and the history of the habitus they conduct. Relational social capital is at stake by assistants with prison officers and how to build relationships with children. Economic capital refers to the efforts made by Sahabat Kapas to get funds to support assistance through entrepreneurship and opening donations. Cultural capital includes the whole intellectual/knowledge gained by assistance through training that is useful to assist children in correctional institutions/detention centers/Institute for Special Development Children (LPKA). Symbolic capital is manifested in the form of awards from the government for Sahabat Kapas and assistance awards for children in the form of gifts.